A SCIENTIFIC JOURNAL OF CHILD CRIMINAL LAW: (Juvenile Justice Criminal Law Policy in Indonesia and Malaysia: A Comparison) - Farhan Taufiqurahman; Handar Subhandi Bakhtiar (Journal of Ius Comparatum Law Studies, 2025)
This paper aims to compare juvenile justice criminal law policies in Indonesia and Malaysia. Child protection is an important aspect of social development and community welfare. In this context, a comparison between these two countries provides valuable insight into child protection approaches, policies and implementation. From the research results, it appears that both countries have serious efforts to protect children's rights. However, there are differences in legal approaches and implementation of child protection policies. In Indonesia, there are regulations governing child protection, such as Law Number 23 of 2002 concerning Child Protection, while in Malaysia, there is the 2001 Children's Act which regulates children's rights. Both countries have their own characteristics in dealing with children in conflict with the law, both in terms of legal basis, institutions and approaches to resolution. This research uses a normative juridical method with a statutory and comparative legal approach. The results of the study show that Indonesia has progressive regulations through the SPPA Law, but still faces challenges in implementation. Meanwhile, Malaysia still applies a relatively conservative and institutional approach.